Radioisotope Evidence of Varying Transit of Solid Food in Gastrectomized Patients with and without Dumping Syndrome - Palermo, F.; Boccaletto, F.; Magalini, M.; Chiara, G.; Tommaseo, T.; Dapporto, L. (Nuklearmedizin - NuclearMedicine, 1988)
Of 29 Billroth II gastrojejunostomy patients studied by scintigraphy, 11 were dumpers and 18 were non-dumpers; of 20 controls, 11 were patients with different gastric complaints and 9 volunteers with no history of gastrointestinal pathology. The tracer used was human albumin microspheres labelled with 99mTc, mixed thoroughly with a fresh scrambled egg, cooked as an omelet and eaten as a sandwich with white toasted bread. The transit and emptying of the radiolabelled meal in the gastric and derivative loop areas were followed with a gamma camera 90-120 min. In the dumpers half-emptying times were significantly shorter than in the controls; in the non-dumpers they were even shorter. Dynamic selective analysis of the radiolabelled food transit through derivative afferent and efferent loops showed, on the other hand, different patterns for the two groups of gastroresected patients: the progression of propulsive waves was very irregular and constantly hyperperistaltic only in the dumpers.Von 29 Patienten, die sich der Billroth II Gastrojejunostomie unterzogen hatten, wiesen 11 das Entleerungssyndrom auf und 18 waren NonDumpers; von 20 Kontrollpatienten klagten 11 über verschiedene Magenbeschwerden und 9 waren Freiwillige ohne gastrointestinale Pathologie. 99mTc-markierte Humanalbumin-Mik- rosphären wurden gründlich mit einem frischen Rührei vermischt, als Omelett gekocht und als Sandwich auf getoastetem Weißbrot verabreicht. Der Transit der so gekennzeichneten Mahlzeit durch den Magen und die anschließenden Darmschlingen wurde mittels Gamma-Kamera während 90-120 min beobachtet. Bei der ersten Gruppe der Gastrektomiepatienten waren die Halbentleerungszeiten deutlich kürzer als bei den Kontrollpatienten und bei den Patienten ohne Dumping-Syndrom noch kürzer. Die dynamisch selektive Analyse des Transits der markierten Mahlzeit durch die zu- und abführenden Darmschlingen zeigte dagegen unterschiedliche Muster für die beiden Gruppen der Gastrektomiepatienten: das Fortschreiten der propulsiven Wellen war nur bei den Patienten mit Dumping-Syndrom unregelmäßig und konstant hyperperistaltisch.